Cost efficiency and endogenous regulatory choices: Evidence from the transport industry in France - Joanna Piechucka (Deutsches Institut für Wirtschaftsforschung (DIW), 2020)
We study the impact of different regulatory designs on the cost efficiency of operators providing a public service, exploiting data from the French transport industry. The distinctive feature of the study is that it considers regulatory regimes as endogenously determined choices, explained by economic, political, and institutional variables. Our approach leans on a positive analysis to study the determinants of regulatory contract choices, which, in turn, affect the costs of operating urban public transport. Our results show that given similar network characteristics, networks operated under fixed-price contracts exert lower costs than those regulated under cost-plus contracts. This finding is in line with the theoretical prediction of new regulatory economics that fixed-price contracts provide more incentives for efficiency. Importantly, ignoring the endogeneity of contractual choices would lead to significantly underestimating the impact of contract type on cost efficiency. Our findings provide useful policy implications suggesting that the move toward more high-powered incentive schemes is indeed associated with significant cost efficiencies. Moreover, they highlights the importance of accounting for the endogeneity of regulatory contract choices.
Keywords: L51; L92; 330; Cost-efficiency; Endogenous contract choices; Transport industry